Ultrasound guidance for radial artery catheterization: an updated meta-analysis of randomized controlled trials. - Lu Tang (Public Library of Science (PLoS), 2014)
Background Since a previous meta-analysis reported that ultrasound guidance was associated with a higher first-attempt success rate in catheterization of the radial artery, a number of randomized controlled trials (RCTs) have reported inconsistent results. The aim of the present study is to conduct an updated meta-analysis to clarify the role of ultrasound guidance for radial artery catheterization. Methods A systematic literature search of PubMed, Embase, and Cochrane Central Register of Controlled Trials was conducted using specific search terms. Eligible studies were RCTs that compared ultrasound guidance with traditional palpation for radial artery catheterization. The Mantel-Haenszel method using the random effects model was adopted in this meta-analysis. Results Seven RCTs with 482 patients were included. Compared with traditional palpation, ultrasound guidance significantly increased the first-attempt success rate of radial artery catheterization (RR 1.51, 95% CI 1.07-2.14, P = 0.02). Subgroup analyses suggested that the superiority of ultrasound guidance for radial artery catheterization was significant when the technique was operated by experienced users, performed in small children and infants, and on elective procedures in the operating room. In addition, ultrasound guidance significantly reduced mean-attempts to success (WMD -1.13, 95% CI -1.58 to -0.69, P<0.00001), mean-time to success (WMD -74.77s, 95% CI -137.89s to -11.64s, P = 0.02), and the occurrence of hematoma (RR 0.17, 95% CI 0.07-0.41, P = 0.0001). Conclusions The present meta-analysis suggests a clear benefit from ultrasound guidance for radial artery catheterization compared with the traditional palpation. Preliminary training and familiarization with the ultrasound-guided technique is needed before applying it for radial artery catheterization, especially for inexperienced operators.